A biological modeling based comparison of two strategies for adaptive radiotherapy of urinary bladder cancer. (2nd August 2016) - Lutkenhaus, L. J.; Vestergaard, A.; Bel, A.; Høyer, M.; Hulshof, M. C. C. M.; van Leeuwen, C. M.; Casares-Magaz, O.; Petersen, J. B.; Søndergaard, J.; Muren, L. P.
Abstract: Background Adaptive radiotherapy is introduced in the management of urinary bladder cancer to account for day-to-day anatomical changes. The purpose of this study was to determine whether an adaptive plan selection strategy using either the first four cone beam computed tomography scans (CBCT-based strategy) for plan creation, or the interpolation of bladder volumes on pretreatment CT scans (CT-based strategy), is better in terms of tumor control probability (TCP) and normal tissue sparing while taking the clinically applied fractionation schedules also into account.Material and methods With the CT-based strategy, a library of five plans was created. Patients received 55 Gy to the bladder tumor and 40 Gy to the non-involved bladder and lymph nodes, in 20 fractions. With the CBCT-based strategy, a library of three plans was created, and patients received 70 Gy to the tumor, 60 Gy to the bladder and 48 Gy to the lymph nodes, in 30–35 fractions. Ten patients were analyzed for each adaptive plan selection strategy. TCP was calculated applying the clinically used fractionation schedules, as well as a rescaling of the dose from 55 to 70 Gy for the CT-based strategy. For rectum and bowel, equivalent doses in 2 Gy fractions (EQD2) were calculated.Results The CBCT-based strategy resulted in a median TCP of 75%, compared to 49% for the CT-based strategy, the latter improving to 72% upon rescaling the dose to 70 Gy. A median rectum V30Gy (EQD2) of 26% [interquartile range (IQR): 8–52%] was found for the CT-based strategy, compared to 58% (IQR: 55–73%) for the CBCT-based strategy. Also the bowel doses were lower with the CT-based strategy.Conclusions Whereas the higher total bladder TCP for the CBCT-based strategy is due to prescription differences, the adaptive strategy based on CT scans results in the lowest rectum and bowel cavity doses.